Kolerasi Intuisi Syaikhona Muhammad Kholil Al-Bangkalani dengan Epistemologi Islam Perspektif Muhammad Abid Al-Jabiri - Moh Ali Ghafir (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2022)
This study aims to determine the scientific basis of knowledge experienced by Syaikhona Muhammad Kholil Al Bangkalani in the form of experiences beyond reason. If there are proofs through scientific studies, then that knowledge becomes scientifically authoritative knowledge. Because Syaikhona Muhammad Kholil is a role model for many people and they already consider his knowledge to be authoritative knowledge without a scientific basis. It is a philosopher Muhammad Abid Al Jabiri who initiated the trilogy of Islamic epistemology consisting of bayani, burhani and irfani epistemology that can answer this problem. With the concept of irfani epistemology conceptualized by Al Jabiri, Syaikhona Muhammad Kholil's intuition knowledge becomes scientifically authoritative. This research uses a leatherative approach by collecting data from various library sources such as books, manuscripts of Syaikhona Muhammad Kholil, journals, historical stories and so on. All data collected is formed into a narrative so that it becomes a finding according to the goal.